Slovenci v vrstah britanskih komandosov - Torkar, Blaž (Acta Histriae, 2020)
This article focuses on the causes for the formation of the British commandos during the Second World War and in particular the functioning of the 10th Inter-Allied Commando, which included No. 7 (Yugoslav) Troop, mostly comprised of Slovenes. No. 7 Yugoslav Troop was formed to conduct military operations in the Mediterranean and the Adriatic. It was composed of selected volunteers from the Yugoslav Royal Guard Battalion who wanted to liberate their homeland alongside the Allies. From among the commandos trained and selected, the British planned to send at least twenty-three Slovenes and two Croats into combat, separately in two groups. The first group only ended up fighting on the Dalmatian islands in early 1944, whereas the other did not fight at all. The reason for this was that the majority wanted to join the Partisans and help them liberate Yugoslavia. No. 7 Yugoslav Troop did not entirely meet the British expectations. Because of the problems described, the Slovenian and Croatian commandos were withdrawn from Yugoslavia and their troop was disbanded on April 15th, 1944. The British authorities thus assigned them elsewhere, but ultimately eighteen of them succeeded in being included as members of the overseas brigades in dispatching aid to the Partisans from June 1944 onward. The fate of seven remains unknown. The literature on the overseas brigades only reveals that six of them continued as commandos in other British units.
Keywords: 2. sv. vojna; 2nd World War; britanski komandosi; British commandos; Jugoslavija; overseas brigades; posebne enote; prekomorske brigade; Slovenci; Slovenians; special forces; Vis; Yugoslavia